بيولوجيا بسيلا أوكاليبتوس الصمغ الأحمر ذات القلنسوة Glycaspis brimblecombei Moore, 1964 (Hemiptera: Aphalaridae) في محافظة اللاذقية، سورية. - أبوكف نبيل; محمد إياد (Latakia University Journal -Biological Sciences Series, 2016)
تم في هذا البحث التسجيل الأول لحشرة بسيلا أوكاليبتوس الصمغ الأحمر ذات القلنسوة Glycaspis brimblecombei Moore, 1964 (Hemiptera: Psylloidea: Aphalaridae) على أوراق أشجار الاوكاليبتوس الأحمر Eucalyptus camaldulensis (Myrtaceae) في سورية. تم جمع الحشرة من الأوراق والنموات الحديثة والقديمة لأشجار الاوكاليبتوس من ثلاث مواقع في محافظة اللاذقية خلال شهر حزيران/ يونيو من عام 2015. تم توضيح صفات المظهر الخارجي للحشرات وقورنت بالمفاتيح التصنيفية المتخصصة. أظهرت النتائج أن أعلى متوسط لمجموعات بيوض البسيلا كان في موقع بستان الباشا على السطح السفلي للأوراق وبلغ 5.80±2.00 مجموعة، وكان أعلى متوسط لأعداد البيوض في الموقع ذاته على السطح السفلي للأوراق أيضاً وبلغ 65.80±47.97 بيضة/ورقة. كان أعلى متوسط لأعداد الحوريات تحت القلنسوة البيضاء في موقع بستان الباشا على السطح السفلي للأوراق حسب أعمارها كما يلي: L1: 18.4±9.51، وL2: 9.60±3.32، وL3: 6.40±0.92، بينما L4: 2.80±1.74 على السطحين العلوي والسفلي. كان أعلى متوسط لأعداد حوريات البسيلا بدون قلنسوة بيضاء للحورية الأولى L1: في موقع شهد العسل على السطح السفلي 3.40±0.87، وL2: في الموقع ذاته على السطح العلوي 5.80±2.43، وL3: في موقع بستان الباشا على السطح السفلي 2.80±0.58، وL4: في موقعي شهد العسل وبستان الباشا 0.20±00.2 على السطح العلوي والسفلي. كان أعلى متوسط لأعداد الحشرات الكاملة في موقع بستان الباشا على السطح العلوي 1.40±1.16، وأقلها في موقع شهد العسل على السطح العلوي 0.20±0.20. In this research, the occurrence of Glycaspis brimblecombei Moore (Hemiptera: Psylloidea: Aphalaridae) was recorded for the first time on Eucalyptus camaldulensis (Myrtaceae) leaves in Syria. Where collected from the leaves and shoots of young and old trees of eucalyptus from Lattakia province in June 2015 in three sites. The morphological characters examined and compared with the specialized keys for this species. The results showed that the highest average for psyllid egg masses was in Bustan AlBasha on the lower surface of the leaves and amounted to 5.80±2.00 mass, had the highest average number of eggs in the same location and on the lower surface also reached 65.80±47.97 eggs / Leaf. The highest average number of nymphs under the Lerp in Bustan AlBasha on the lower surface of the leaves as stage as follows: L1: 18.4±9.51, and L2: 9.60±3.32, and L3: 6.40±0.92, while L4: 2.80±1.74 on the upper and lower surfaces. The highest average number of psyllid nymphs without white Lerp was for the first nymph L1: In Shahd Alaasal site on the Lower surface 3.40±0.87, and L2: at the same previous location on the upper surface of 5.80±2.43, and L3: in Bustan AlBasha site on the Lower surface 2.80±0.58, and L4: in Shahd Alaasal and Bustan AlBasha 0.20±0.20 on the upper and lower surface. The highest average number of adult in the site Bustan AlBasha on the upper surface of 1.40±1.16, and the lowest in the site Shahd Alaasal on the upper surface of 0.20±0.20.